Full-scale validation of the hydrodynamic motions of a ship derived from a numerical hindcast. (15th November 2018) - Milne, I.A.; Zed, M.
Abstract: New measurements from a drillship operating in a swell dominated region are used to demonstrate that generally reliable estimates of the hydrodynamic motions can be obtained from numerically hindcast directional wave spectra. Independent estimates of the directional wave spectra derived from the ship motions using a parametric approach are shown to be in close alignment with the hindcast spectra. Deviations between predictions and observations in this methodology are largely explained through the idealised nature of the hindcast spectra and limitations in the ability of the numerical model to capture swell arrival over the long fetch on approach to the project site, which is demonstrated through comparison of observed and modelled spectra. In general, the study provides encouraging support for the application of numerical hindcast techniques for vessel motion assessments, particularly for sites for which wave buoy measurements are not available. Highlights: Full-scale measurements of a drillship enabled validation of numerically derived responses. Hindcast wave spectra are shown to yield reliable estimates of the hydrodynamic motions. Wave spectra derived from the ship motions are in close alignment with hindcasts. Idealised nature and limitations of hindcasts largely explain deviations in predictions.